In vivo anti-tumor activity of the PARP inhibitor niraparib in homologous recombination deficient and proficient ovarian carcinoma(,) - AlHilli, Mariam M. (Gynecol Oncol, 2016)
OBJECTIVE: Poly(ADP-ribose) polymerase (PARP) inhibitors have yielded encouraging responses in high-grade serous ovarian carcinomas (HGSOCs), but the optimal treatment setting remains unknown. We assessed the effect of niraparib on HGSOC patient-derived xenograft (PDX) models as well as the relationship between certain markers of homologous recombination (HR) status, including BRCA1/2 mutations and formation of RAD51 foci after DNA damage, and response of these PDXs to niraparib in vivo. METHODS: Massively parallel sequencing was performed on HGSOCs to identify mutations contributing to HR deficiency. HR pathway integrity was assessed using fluorescence microscopy-based RAD51 focus formation assays. Effects of niraparib (MK-4827) on treatment-naïve PDX tumor growth as monotherapy, in combination with carboplatin/paclitaxel, and as maintenance therapy were assessed by transabdominal ultrasound. Niraparib responses were correlated with changes in levels of poly(ADP-ribose), PARP1, and repair proteins by western blotting. RESULTS: Five PDX models were evaluated in vivo. Tumor regressions were induced by single-agent niraparib in one of two PDX models with deleterious BRCA2 mutations and in a PDX with RAD51C promoter methylation. Diminished formation of RAD51 foci failed to predict response, but Artemis loss was associated with resistance. Niraparib generally failed to enhance responses to carboplatin/paclitaxel chemotherapy, but maintenance niraparib therapy delayed progression in a BRCA2-deficient PDX. CONCLUSIONS: Mutations in HR genes are neither necessary nor sufficient to predict response to niraparib. Assessment of repair status through multiple complementary assays is needed to guide PARP inhibitor therapy, design future clinical trials and identify ovarian cancer patients most likely to benefit from PARP inhibition.